Offshore Wind Farm Layout Optimization Considering the Power Collection System Cost - S. G. Obukhov; D. Y. Davydov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes a method for optimizing the layout of offshore wind farms to increase their efficiency by reducing the effect of aerodynamic shading, minimizing electrical losses in cable lines of the system for receiving and transmitting electrical energy generated by wind turbines to the electrical grid of the power system. The task is reduced to determining several parameters that define the geometric dimensions and shape of the layout grid with pre-installed tur-bine locations. This approach, in contrast to the coordinate-wise search method, makes it possible to build symmetrical grid layouts of wind power plants, which in practice are more convenient in terms of maintenance and operation. Together with the optimization of the layout, the search for the optimal location of the offshore transformer substation and the synthesis of the scheme of cable joints between wind power plants has been carried out. To solve this problem, a heuristic algorithm was used to search for a minimum spanning tree with a restriction on the conductivity of connections, which made it possible to build realistic schemes and more adequately assess their technical and economic characteristics. As the results of testing the proposed methodology on the example of optimizing the layout of the Horns Rev 1 wind farm have shown, the use of this approach has reduced the cost of the electrical system by 10–12 %. This is 7–11 % higher than the result obtained by using the MST algorithm, which performs the construction of a circuit of cable joints of a simplified topology. The change in the size and shape of the boundaries of the wind farm site resulted in an increase in the estimated electricity generation by 2.3 % and a decrease in its cost by 4 %. When optimizing the layout of wind turbines within the fixed boundaries of the site, these indicators are improved by only 1 and 2 % as compared to the original scheme.